Gender Issues in Language Learning - Davronova Asila Yusuf qizi (Periodica Journal, 2022)
Gender and education is a broad category where several thematic strands of inquiry emerge: socialization in schools, the social experience of schooling, textbooks, books, curriculum, educational attainment, educators/education workers, higher education, and cross-cultural educational practices. Many of the articles in each of these sub-categories may also be cross-referenced across these thematic areas as well. An interesting trend in the scholarship is the movement from primarily gender studies in the early days of Gender-Society, to a greater intersectional contemporary focus as well as increased scholarship contexts.
Keywords: Gender bias; pedagogical level; gender issues